A novel proteinase from human pancreas. - Sziegoleit, A (1984)
A cholesterol-binding protein was previously isolated from human pancreas [Sziegoleit (1982) Biochem. J. 207, 573-582] and shown to consist of a single polypeptide chain with an apparent Mr of 28 000 and an isoelectric point of pH 4.9. In further investigations, a proteolytic activity was observed to be present in preparations of this protein. The enzyme activity was not dissociable from the cholesterol-binding protein. It decreased in the presence of sodium dodecyl sulphate or urea parallel to degradation of the protein, indicating autodegradation in the presence of these denaturants. Glucagon digestion studies indicated the carbonyl bond of alanine to be a favoured site of the enzymic cleavage. The proteinase was inactive against chromogenic substrates relatively specific for elastase, trypsin and chymotrypsin, but was found to cleave benzyloxycarbonylalanine p-nitrophenyl ester efficiently. The enzyme was inactivated by phenylmethanesulphonyl fluoride and was thus classified as a serine proteinase. Autoradiographic studies demonstrated binding to serum alpha 1-antitrypsin and alpha 2-macroglobulin in a similar manner to that observed with other pancreatic endo-proteinases. The collective results indicate that the isolated protein, provisionally named 'cholesterol-binding pancreatic proteinase', is a novel proteinase of the human pancreas. Quantitative measurements indicate that it comprises 4-6% of total protein in pancreatic secretions.